CD39/CD73 upregulation on myeloid-derived suppressor cells via TGF-β-mTOR-HIF-1 signaling in patients with non-small cell lung cancer. (3rd June 2017) - Li, Jieyao; Wang, Liping; Chen, Xinfeng; Li, Lifeng; Li, Yu; Ping, Yu; Huang, Lan; Yue, Dongli; Zhang, Zhen; Wang, Fei; Li, Feng; Yang, Li; et al.
ABSTRACT: CD39/CD73-adenosine pathway has been recently defined as an important tumor-induced immunosuppressive mechanism. We here documented a fraction of CD11b + CD33 + myeloid-derived suppressor cells (MDSCs) in peripheral blood and tumor tissues from non-small cell lung cancer (NSCLC) patients expressed surface ectonucleotidases CD39 and CD73. Tumor TGF-β stimulated CD39 and CD73 expression, thereby inhibited T cell and NK cell activity, and protected tumor cells from the cytotoxic effect of chemotherapy through ectonucleotidase activity. Mechanistically, TGF-β triggered phosphorylation of mammalian target of rapamycin, and subsequently activated hypoxia-inducible factor-1α (HIF-1α) that induced CD39/CD73 expression on MDSCs. CD39 and CD73 on MDSCs, therefore, link their immunosuppressive and chemo-protective effects to NSCLC progression, providing novel targets for chemo-immunotherapeutic intervention.